AB0256 Very Early Response To Abatacept Could Be A Predictive Factor for Repair of Bone Erosion in Patients with Rheumatoid Arthritis Assessed by MRI. (15th July 2016) - Kukida, Y.; Kasahara, A.; Seno, T.; Inoue, T.; Kamio, N.; Sagawa, R.; Kida, T.; Nakabayashi, A.; Nagahara, H.; Yamamoto, A.; Morita, S.; Ito, H.; et al.
Abstract : Background: There is no report investigating predictive factors for MRI erosion change in treatment of rheumatoid arthritis (RA) with abatacept (ABT), because very little data are available on the efficacy of ABT assessed by MRI. Objectives: The aim of this study is to examine the efficacy of ABT in patients with RA assessed by MRI and identify factors associated with change of bone erosion score. Methods: Thirty-five RA patients were included in this prospective study. MRI of bilateral hands and conventional radiographs (CR) of bilateral hands and feet were performed at baseline and month 12 of treatment with intravenous ABT. MRI images were scored for synovitis, osteitis and bone erosion according to the Rheumatoid Arthritis MRI Scoring System. CR images were assessed according to the van der Heijde modified total Sharp score. Results: Thirty-one patients completed this study. Mean Simplified Disease Activity Index (SDAI) and Health Assessment Questionnaire Disability Index (HAQ-DI) at baseline were 23.4±12.0 and 1.1±0.6 respectively. At the group level, mean MRI synovitis and osteitis scores showed statistically significant reductions through 12 months of treatment with ABT (from 17.1±7.0 to 11.4±6.2 (p<0.0001) and from 5.1±8.2 to 1.9±2.5 (p=0.003), respectively). On the other hand, mean MRI erosion scores showed no change throughout the study period (from 28.2±38.6 to 28.7±39.2). Mean CR erosion scores also showed no change (from 17.3±42.5 to 17.6±42.6). However, at the patient level, reductions of MRI erosion score were observed in 13% of patients, whereas no patient showed reduction of CR erosion score. The functional remission rates, which is defined as HAQ-DI≤0.5, of patients with regressive, unchanged and progressive MRI erosion score were 100%, 71% and 33%, respectively. On multiple regression analysis, SDAI response rate at month 1 and CRP at baseline were identified as the predicting factors for changes of erosion score (regression coefficient; -0.70 (p<0.001)/0.42 (p=0.02), respectively). Optimal cutoff value of SDAI response rate at month 1 was 0.524 (p=0.019). It is interesting that patients with regression of MRI erosion had high titer of rheumatoid factor (median: 591IU/ml) and anti-CCP antibody (median: 254U/ml) at baseline. Conclusions: This study demonstrated ABT has a strong inhibitory effect on joint damage reducing synovitis and osteitis and not progressing bone erosion in RA patients. Over 10% patients showed repair of bone erosion assessed by MRI, which resulted in functional remission. SDAI response rate at month 1 could be a predictive factor for repair of bone erosion. Disclosure of Interest: Y. Kukida Grant/research support from: Bristol-Myers Squibb, A. Kasahara: None declared, T. Seno: None declared, T. Inoue: None declared, N. Kamio: None declared, R. Sagawa: None declared, T. Kida: None declared, A. Nakabayashi: None declared, H. Nagahara: None declared, A. Yamamoto: None declared, S. Morita: None declared, H. Ito: None declared, M. Kohno: None declared, Y. Kawahito Grant/research support from: Bristol-Myers Squibb